Association of relationship satisfaction with blood pressure: a cross-sectional study of older adults in rural Burkina Faso - Jaspert, Felicitas Maria; Harling, Guy; Sie, Ali; Bountogo, Mamadou; Bärnighausen, Till; Ditzen, Beate; Fischer, Melanie (BMJ open, 2024)
Objectives The objective of this study is to examine the association between relationship satisfaction and blood pressure (BP) in a low-income setting and to screen for gender moderation in this context. Research conducted in high-income settings suggests that relationship satisfaction is associated with better physical and mental health outcomes. - Design A cross-sectional study design was employed, using both questionnaire and physical measurement data. Multiple linear regression models were calculated for systolic and diastolic BP and adjusted for age, gender, demographics/socioeconomics and other health-related variables. Gender moderation was tested using interaction terms in multivariable analyses. - Setting A household survey was conducted in 2018 in rural northwestern Burkina Faso. - Participants Final analysis included 2114 participants aged over 40 who were not pregnant, reported being in a partnership and had valid BP readings. - Main outcome measures Systolic and diastolic BP levels. - Results A significant positive association existed between relationship satisfaction (Couples Satisfaction Index-4 score) and systolic BP (B=0.23, 95% CI (0.02 to 0.45), p=0.03) when controlling for demographics/socioeconomics. Nevertheless, this relationship lost statistical significance when additional adjustments were made for health-related variables (B=0.21, 95% CI (−0.01 to 0.42), p=0.06). There was no significant association of relationship satisfaction and diastolic BP and no evidence of gender moderation. - Conclusion In contrast to many higher-income settings, we found a positive association between relationship satisfaction and systolic BP in very low-income rural Burkina Faso. Our results add to the evidence regarding the contextual nature of the association between relationship satisfaction and health, as high relationship satisfaction may not act as a health promotor in this socioeconomic context.